PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Dewi, Noviyanti; Sastri, Enan Trivansyah (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze and provide empirical evidence regarding the influence of firm size, managerial ownership, and sales growth on tax avoidance. This research is quantitative in nature, utilizing secondary data in the form of financial statements, which contain numerical figures that are tested and described to illustrate the results. The sample selection employs purposive sampling technique. The data analysis method used is panel data regression, processed using Eviews version 9. The population in this study consists of manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023, totaling 543 companies. The obtained sample consists of 13 companies over a five-year study period, resulting in a total of 65 data points. The results indicate that firm size and managerial ownership do not significantly influence tax avoidance, while sales growth does have an effect on tax avoidance. Collectively, the variables of firm size, managerial ownership, and sales growth significantly impact tax avoidance. The benefit of this research is that it provides a deeper understanding of the factors that influence tax avoidance and offers practical insights that can be used by various parties, from policy makers, company managers, to investors.